Does vertical integration of health and social care organizations work? Evidence from Scotland. (August 2022) - Alonso, José M.; Andrews, Rhys
Abstract: Vertical integration of health and social care organizations is widely regarded as an effective way to deliver improved outcomes for recipients of the services provided by those organizations. We test this hypothesis by investigating the impact of the creation of integration authorities in Scotland – statutory bodies responsible for planning and resourcing adult social care, primary care, community health and unscheduled hospital care at the local level. Employing a difference-in-difference style analysis we compare delayed discharges and premature mortality rates in Scottish integration authorities with those for local authority areas in the North of England for the period 2013–2019. The results suggest that health and social care integration led to improved performance on delayed discharges in Scotland (point estimate, −0.236; 95% confidence interval, −0.443, −0.029), but that premature mortality rates remained unchanged. These findings suggest that the vertical integration of local health and social care organizations may enhance organizational efficiency and patient experience, but that improvements on broader indicators of population health are more difficult to achieve. Highlights: Vertical integration of health and social care can enhance patient outcomes. Delayed discharges fell after the creation of statutory integration authorities. Premature mortality is unaffected by vertical integration of health and social care.